Allie Cole : a Maine pioneer - Cole, Galen L. (Portland, Me. : Casco Printing Co., 1980)
This is the story of Albert J. Cole, the founder of Cole's Express, the man who influenced the trucking industry and the delivery of goods and services in central and northern Maine
Keywords: Cole, Albert J., -- 1893-1955.; Cole's Express. LEADER 00000nam 2200000Ii 4500; Trucking -- Maine -- History; Maine -- Biography